The Dilemma of Sharia Compliance in Bangladesh: An Empirical Legal Study - Nurunnabi, Muhammad (International Journal of Sharia Studies, 2025)
Ideally, the Islamic legal system in Bangladesh is expected to serve as both a moral and juridical foundation for the formulation of public policies and the governance of financial institutions. However, in reality, the implementation of Sharia principles continues to face a dilemma between normative idealism and legal practices influenced by secularism, identity politics, and the legacy of the British colonial legal system. This study aims to analyze the level of Sharia compliance in Bangladesh by highlighting the social, political, and institutional factors that influence it. This research is a literature-based study employing a descriptive qualitative approach, using primary sources such as scholarly journals and legal documents related to the implementation of Sharia in financial institutions and the legislative system of Bangladesh, and secondary sources including research reports and international academic publications. The findings reveal that the dilemma of Sharia compliance in Bangladesh stems from the lack of synchronization between the aspirations for legal Islamization and the dominance of a secular legal framework. Nevertheless, constructive efforts have been made through institutional reforms, scholarly fatwas, and Islamic banking policies to bridge this gap.